REPRESENTAMEN OF MORALITIES ON LANGUAGE AND VISUAL SIGNS IN INCREDIBLES 2 FILM - Diyanto, Assyafa Puteri; Nurulaen, Yuyun; Rusmana, Dadan (CALL, 2023)
Film stands out as a compelling contemporary mass medium that has witnessed substantial growth. This progress has given rise to numerous film genres, intended to captivate audiences across generations, including the realm of animated cinema. Often, films convey messages depicting the dichotomy between good and bad characters in everyday life, typically portraying the vulnerable and kind-hearted individuals facing oppression from self-centered antagonists. However, in fictional works like "Incredibles 2," superheroes emerge as guardians, shielding society from menacing forces. This research aimed to provide a comprehensive elucidation of the interpretive process through the utilization of the triadic model. Furthermore, it endeavors to discern the facets of morality manifested through both linguistic and visual symbols within the semiotic framework of the movie "Incredibles 2." This was about semiotics which refers to Charles Sanders Peirceâ€™s theory. This study used qualitative method as research design. Data in the study were signs appeared in the film. The findings section showed six kinds of sign that the writer founded in the Incredibles 2 film which are sinsign, qualisign, legisign, icon, indexes, and symbol that exists moralities signs. The findings on sign can divided into two parts, Language and Visual sign. Language sign can be utteranced by the speaker on the film from Mr. Incredible and a little boy. Visual sign could be shown by icon and symbol on the things in every capture.Â Keywords: semiotic, Pierce, moralities, Incridibles 2